(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2026)
Reducing hunger is one of the primary targets of the Sustainable Development Goals (SDGs), particularly Goal 2: Zero Hunger. The Global Hunger Index (GHI) is a key indicator used to measure hunger, comprising four components: the prevalence of undernourishment (PoU), child mortality rate, child stunting, and wasting. While PoU and child mortality data are available at the district/city level across Indonesia, limited data on stunting and wasting in several makes it difficult to calculate the GHI at the local level. Data limitations hinder the formulation of locally targeted policies. This study aims GHI in Papua Province using the Small Area Estimation (SAE) approach. Data sources include the 2023 Indonesia Health Survey and Podes 2021. , while wasting is estimated using the Hierarchical Bayes Beta approach. that SAE improves estimation precision compared to direct estimation, as reflec by . Estimates reveal GHI may vary in category between serious to extremely alarming, with Jayapura City having the lowest and Dogiyai as the highest GHI in Papua.